Extraversion and Neuroticism on College Freshmen's Depressive Symptoms During the COVID-19 Pandemic: The Mediating Role of Social Support - Yu, Tengxu; Hu, Jinsheng (Frontiers in Psychiatry, 2022)
Objective: This study aims to explore the direct effects of extraversion and neuroticism on college freshmen’s depressive symptoms and their indirect effects via social support under the background of COVID-19. Method: A total of 3563 college freshmen were surveyed using the extraversion and neuroticism scales of the Chinese version of the Eysenck Personality Questionnaire (EPQ), the Chinese version of the Beck Depression Inventory-II (BDI-Ⅱ), and the Social Support Rating Scale (SSRS). Partial correlation analyses and regression analyses were used. Results: (1) Extraversion had a significant and negative predictive effect on depressive symptoms, while neuroticism positively predicted depressive symptoms. The interaction effect between extraversion and neuroticism on depressive symptoms was also significant. Neuroticism had a greater impact on depressive symptoms in college freshmen with low levels of extraversion. (2) Furthermore, social support partially mediated the relationships between extraversion and depressive symptoms, and neuroticism and depressive symptoms. Conclusions: Extraversion and neuroticism can directly affect college freshmen’ s depressive symptoms, and have indirect effects via the mediating role of social support. Additionally, extraversion interacts with neuroticism, and extraversion plays a protective role in the effect of neuroticism on depressive symptoms. These findings help identify college freshmen at high risk of depression and design effective prevention or intervention measures for them.